COVID-19 responses and coping in young Malaysians from low-income families - Wong, Li Ping; Farid, Nik Daliana Nik; Alias, Haridah; Yusop, Sofia Md; Musa, Zuhrah; Hu, Zhijian; Lin, Yulan (Frontiers in Psychiatry, 2023)
Introduction This study aimed to shed light on how young people from low-income families were responding to COVID-19. Methods This cross-sectional study recruited young people aged between 18 and 24 years from the low-income-group communities. A convenience sampling approach was used. Google Surveys were used to gather data from the survey. The questionnaire consisted of an assessment of demographic characteristics, lifestyle factors, parent–youth conflict (Parental Environment Questionnaire, PEQ), resilient coping (Brief Resilient Coping Scale, BRCS), and psychological distress (Depression, Anxiety, and Stress Scale-short form, DASS-21). Results A total of 561 complete responses were received. The results showed a low level of parent–child conflict in the overall study population, with a median PEQ of 48.0 [interquartile range (IQR) 36–48]. Higher parent–child conflicts were found in females than in males (OR = 1.75, 95% CI 1.19–2.57) and in youth from households with an income below MYR 2000 than those earning MYR 3,001–5,000 (OR = 4.39, 95% CI 2.40–8.03). A low prevalence of depression (12.5%), anxiety (15.2%), and stress (6.4%) was found. Parent–child conflict remains the strongest significant predictor for higher levels of depression (OR = 10.90, 95% CI 4.31–27.57), anxiety (OR = 11.92, 95% CI 5.05–28.14), and stress (OR = 4.79, 95% CI 1.41–16.33) symptoms. Poor resilient coping was the second strongest predictor for depression and anxiety symptoms. Regarding lifestyle factors, a lower level of physical exercise was associated with higher symptoms of depression. By demographics, females reported more severe symptoms of depression and anxiety than males. Young people from low-income households reported greater severity in symptoms of depression, anxiety, and stress than those from high-income households. Young people who are employed also reported greater severity of anxiety symptoms than those who are unemployed. Discussion The COVID-19 pandemic continues to have an unpredictable impact on the lives of vulnerable youth in low-income families that warrants attention in future advocacy efforts.